2013
DOI: 10.1002/edn.226
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes research reported by nurses in Nordic countries

Abstract: New knowledge from research studies is important as a foundation for high‐quality care in practice as well as crucial to further stimulate research in the future. The aims of this study were to determine the total number of peer‐reviewed articles on diabetes research reported by nurses in four Nordic countries (Denmark, Iceland, Norway and Sweden) from 1979–2009, and to identify the time periods in which they had been published, different study designs and the number of publications related to nurse authors. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Also, action is needed to build stronger research networks across national borders. We have previously shown that only 14% of the studies included co‐authors from another country .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, action is needed to build stronger research networks across national borders. We have previously shown that only 14% of the studies included co‐authors from another country .…”
Section: Discussionmentioning
confidence: 99%
“…Goodman and Moule describe how nursing research has a keen interest in what patients feel and experience, how nurses learn and develop throughout their careers and how multidisciplinary working and learning contributes to the care of patients. In a previous study, we discussed issues related to the development of diabetes nursing research in Nordic countries and the development of professional research competence and the pace of progress in building nursing research collaboration across national borders . Thus, the present study aims to review the entire body of scientific publications in the field of diabetes nursing research that has been conducted in four Nordic countries: Norway, Sweden, Denmark and Iceland.…”
Section: Introductionmentioning
confidence: 99%
“…The third domain encompasses diseases where nursing research is scarce, and as a result, more research is urgently called for. Stroke (Lightbody, 2017;Rowat et al, 2016), heart failure (Stamp et al, 2018), Parkinson's disease (Shin & Habermann, 2016), osteoarthritis (Robbins & Kulesa, 2012), diabetes (Graue et al, 2013;Iversen et al, 2016) and stoma (Hubbard et al, 2017) are considered to be the above-mentioned areas of diseases. With respect to nursing research on diabetes, Iversen et al (2016) believe that future research may benefit from larger nurse-led research programmes organized into networks to share knowledge and expertise across national groups.…”
Section: Diseases and Specific Fields From The Nursing Perspectivementioning
confidence: 99%
“…. Graue et al (2013) in their analysis of Diabetes research in four Nordic countries (Denmark, Iceland, Norway and Sweden) from 1979 -2009 show that " … International collaborative research networks facilitate funding opportunities and contribute to further development of professional research competence." .…”
Section: Literature Review On Influence Of Collaboration On Research mentioning
confidence: 99%